Impact of “intensive parenting attitude” on children’s social competence via maternal parenting behavior - Egami, Sonoko (Frontiers in Psychology, 2024)
“Intensive parenting” is a tendency to invest parents’ time, money, and energy in their child. This also includes some gender bias concerning a mother being the best person to primarily raise her children. Some psychology scholars have pointed out that this attitude causes much stress, anxiety, depression, and a sense of guilt among mothers. However, its effects on children have yet to be revealed using an extensive survey, and this indicates the need to investigate any possible impact of an intensive parenting attitude on children. The aim of this study was to elucidate a link between a maternal intensive parenting attitude and their children’s social competence through maternal parenting behavior. This was based on collecting data from 675 Japanese women who were mothers of preschoolers using the Japanese version of the Intensive Parenting Attitude Questionnaire, the Positive and Negative Parenting Scale, and the Strength and Difficulties Questionnaire. The results showed that the “Essentialism,” “Fulfillment,” and “Child-centered” components of intensive parenting attitude influenced the “involvement and monitoring” and “positive responsivity” of parenting behavior. Furthermore, these two parenting behaviors affected children’s prosocial behavior and hyperactivity/inattention. These findings suggest that an intensive parenting attitude has some impact on children as well as mothers, both positively and negatively, pointing to a serious effect on society.